Pertumbuhan Tomat pada Frekuensi Pengairan yang Berbeda - Riana Jumawati; Amalia Tetrani Sakya; Muji Rahayu (Agrosains : Jurnal Penelitian Agronomi, 2014)
Tomato (Lycopersicum esculentum Mill) is one of horticulture commodities with high economic value and still need seriously handling especially for increasing fruits quality and quantity. However the production of tomato has not fullfilleed the demand yet. Therefore it is necessary to develop production. On lowland, the issue not only high temperature but also availability of water is unpredictable.This study aimed to investigate the effect of irrigation frequency on the growth of Mutiara, Opal, and Gondol tomato variety. This research was conducted at the Greenhouse Laboratory of the Agriculture Faculty, Sebelas Maret University with attitude 95 m asl. Implementation of the research conducted from January to May 2013. This research used completely randomized factorial design with two factors, namely variety of tomato (Gondol, Opal and Mutiara) and watering frequencies (everyday, once in 3 days, once in 6 days, and once in 9 days). The results showed that plant height, number of leaves and number of branches are influenced by the variety of tomato and irrigation frequency, whereas chorophyl content is influenced by the watering frequency. Growth component and chlorophyll content of tomato decreased with increasing irrigation frequency.